Violência contra as mulheres e masculinidades: questões de gênero - THIAGO DE BRITO RIBEIRO (2024)
This work deals with the possible correlations between the categories of gender, gender-based violence against women and masculinity. Its starting point is the psychosocial phenomenon of gender-based violence against women, its historical-cultural determinations and gender relations. The epistemological basis underlying this study consists of the so-called Feminist Criticism, which is a type of critical feminist epistemology that takes into account the determinations of the patriarchal ideological system that brings as one of its consequences, unequal relations of power and opportunities between genders: gender-based violence against women can be one of these consequences. This research resulted in three scientific articles, namely: article 01 – theoretical essay based on a narrative literature review on the ideological system of patriarchy and concepts regarding the gender category; article 2 – theoretical essay based on a narrative review of literature on gender-based violence against women, masculinities and reflective groups of men who commit domestic and family violence; article 3 – documentary research, consisting of a systematic and integrative literature review to answer the question “what have Psychology journals published about the interrelations between gender, gender-based violence against women and masculinity?”. In relation to the last article, a systematic and integrative literature review was carried out with the following inclusion criteria: (1) articles published in the journals chosen for documentary research; (2) publications between 2016 and 2022; (3) complete articles; (4) articles with keywords and themes related to the descriptors “gender”, “gender violence” and “masculinities”. To organize and analyze the data, L. Bardin's Content Analysis method was used. After separating the articles found into Thematic Categories, it was identified that the publications discussed the topic studied here from different angles, with no unanimity regarding the use of the terms “gender violence”, “violence against women”, “ domestic and family violence against women”, which makes it difficult to understand the phenomenon of violence against women globally. Most articles present a gender discussion about violence against women and masculinities. Also in most publications, masculinities were represented in their hegemonic perspectives, in accordance with Raewyn Connell's postulations. It was observed that few publications were found in the selected Psychology journals, which demonstrates that it is necessary for this area of knowledge to carry out further studies and research, in order to operationalize, in addition to the creation and planning of public policies, interventional actions that aim to to confront gender-based violence against women, as well as proposals to rethink masculinity performances that end up producing violent discourses and practices in society.